Cost-effectiveness analyses of 20-valent pneumococcal conjugate vaccine in children and adults: A narrative review - Aiko Shono; Shu-Ling Hoshi; Masahide Kondo (Human Vaccines & Immunotherapeutics, 2025)
Many pneumococcal vaccines have been developed. Economic evaluation provides a framework to inform decision-making. Cost-effectiveness analysis (CEA) studies on 20-valent pneumococcal conjugate vaccine (PCV20) have been published. We introduce the concept of health economics and the basic framework for CEAs. We present a narrative literature review of recent CEA studies involving the PCV20. We also provide guidance for interpreting vaccine-related CEAs. We included 26 CEAs (17 in adults, nine in children) from 15 countries in this review. Eight of the pediatric studies and 11 of the adult studies concluded that PCV20 strategy would be cost-saving compared with existing vaccine(s), in at least one comparison. CEA is a modeling method based on existing data but includes a degree of uncertainty. It is therefore important to interpret the results of a CEA study with an understanding of the features and limitations of the analysis.